Comparison of clinical practice guidelines for the management of pain, agitation, and delirium in critically ill adult patients. Issue 3 (10th April 2018) - Tsuruta, Ryosuke; Fujita, Motoki
Abstract : Guideline‐based management approaches for pain, agitation, and delirium (PAD) in critically ill adult patients are widely believed to result in good outcomes. However, there are some differences in the recommendations and evidence levels among the management guidelines established for PAD. To identify and compare the current management guidelines, we used the PubMed database. The PAD guidelines and Federación Panamericana e Ibérica de Sociedades de Medicina Crítica y Terapia Intensiva (FEPIMCTI) guidelines were identified from our search. We compared the main aspects of these two guidelines as well as the Japanese guidelines for the management of PAD (J‐PAD guidelines). The PAD, FEPIMCTI, and J‐PAD guidelines contained a total of 4, 12, and 5 sections, having 32, 138, and 37 recommendations, respectively, pertaining to routine monitoring of pain in adult patients in the intensive care unit. Intravenous opioids were recommended as the first‐line drug of choice for treating pain. Sedative titrated to maintain a light, rather than deep, level of sedation can be given unless clinically contraindicated. Although neither the PAD nor J‐PAD guidelines recommend use of a pharmacologic delirium prevention protocol or treatment with any pharmacological agent to reduce the duration of delirium, the FEPIMCTI guidelines provide such recommendations. The FEPIMCTI guidelines provide suggestions on which analgesics to use for several different cases and present algorithms for sedation and analgesia. The outlines of the three guidelines are similar, and all reinforce the management of PAD to improve patient outcomes. Abstract : The outlines of the three guidelines are similar, and all reinforce the management of PAD to improve patient outcomes.